GEOCHEMICAL INDICATORS OF THE MIGRATION OF OIL IN THE EASTERN FORE-CAUCASUS ON THE BASIS OF THE FRACTIONATION OF CARBAZOLES - Frolov Ye.B.; Kasyanova N.A. (My University, 1997)
Research was carried out into the fractionation of carbazoles in oils in connection with the hypothesis that the composition of carbazoles in oils is very sensitive to the process of migration. The original composition of the carbazoles undergoes fractionation as the oils migrate, in particular the 1,8-H and H-isomers are lost. The research comprised a gas-liquid chromatography study of the relationships in the series 1-, 2-, 3-methyl, 1-ethyl and also 1,8-dimethyl carbazoles in oil samples from Lower Cretaceous deposits in seven oil fields in the Prikumsko-Tyulenevskaya zone. The data obtained on changes in the composition of carbazoles supported the wide development of the lateral migration of hydrocarbons and the current formation of hydrocarbon deposits of various phase states in this region.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая